2018
DOI: 10.1080/01480545.2018.1480629
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polydatin and grape seed extract in rats exposed to cadmium

Abstract: The current study aimed to investigate the protective role of polydatin (PD) and grape seed extracts (GSEs) against the effects of cadmium chlorine (CD) application in the rats. Forty-nine adult Wistar albino male rats were used in the study. Rats were assigned into control (saline), CD (5 mg/kg CdCI), PD (120 mg/kg PD), GSE (120 mg/kg GSE), CD + PD (5 mg/kg CdCI + 120 mg/kg PD), CD + GSE (5 mg/kg CdCI + 120 mg GSE), and CD + PD + GSE (5 mg/kg CdCI+120 mg/kg PD +120 mg/kg GSE) treatments (n = 7 per group). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Several studies have identified grape seed extract, grape seed pro-anthocyanidin extract, and grape juice concentrate as protective factors against cadmium toxicity. Grape seed extract and grape seed pro-anthocyanidin extract improved histopathological find-ings [132][133][134][135], increasing the diameter and normal SeT [132,135], testicular weight [132], and Johnsen's mean testicular biopsy score and decreasing the apoptotic index [135]. It was also observed to increase PCNA immunoreactivity [132] and total antioxidant status (TAS) [133] in the enzymes of the antioxidant defense system and genes associated with steroidogenesis and Ki-67 expression [134], and it decreased MDA levels [133,134] and the immunoreactivity of the apoptotic regulator Bax [134].…”
Section: Grapementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified grape seed extract, grape seed pro-anthocyanidin extract, and grape juice concentrate as protective factors against cadmium toxicity. Grape seed extract and grape seed pro-anthocyanidin extract improved histopathological find-ings [132][133][134][135], increasing the diameter and normal SeT [132,135], testicular weight [132], and Johnsen's mean testicular biopsy score and decreasing the apoptotic index [135]. It was also observed to increase PCNA immunoreactivity [132] and total antioxidant status (TAS) [133] in the enzymes of the antioxidant defense system and genes associated with steroidogenesis and Ki-67 expression [134], and it decreased MDA levels [133,134] and the immunoreactivity of the apoptotic regulator Bax [134].…”
Section: Grapementioning
confidence: 99%
“…Grape seed extract and grape seed pro-anthocyanidin extract improved histopathological find-ings [132][133][134][135], increasing the diameter and normal SeT [132,135], testicular weight [132], and Johnsen's mean testicular biopsy score and decreasing the apoptotic index [135]. It was also observed to increase PCNA immunoreactivity [132] and total antioxidant status (TAS) [133] in the enzymes of the antioxidant defense system and genes associated with steroidogenesis and Ki-67 expression [134], and it decreased MDA levels [133,134] and the immunoreactivity of the apoptotic regulator Bax [134]. Grape juice concentrate treatment against cadmium toxicity demonstrated that co-administration restored the testis, epididymis, and ventral prostate weight [136] to normal levels, ameliorating tissue architecture [125,136,137], epididymis epithelium height (caput and cauda regions) [125] and improving sperm parameters such as production, counts, transit time [125], and morphology [136].…”
Section: Grapementioning
confidence: 99%
“…Recent reports highlight that several chelating agents [10], metals [64,65], chemopreventive phytochemicals [66][67][68][69], and natural drugs [70] can reverse Cd-induced liver cytotoxicity and prevent liver damage (Figure 1). For example, the lipophilic chelating agent MiADMSA can promote the elimination of heavy metals (lead, cobalt, cadmium, manganese, iron, and copper) in the urine of hepatitis C virus (HCV) patients suggesting that chelation therapy could be useful to reverse heavy metal-related health problems [71].…”
Section: Acute Hepatotoxicity Can Be Reversiblementioning
confidence: 99%
“…They are oligomeric compounds formed from catechin and epicatechin molecules, and have many other activities including antibacterial, antiviral, anticarcinogenic, anti-inflammatory, anti-allergic, and vasodilatory actions (Fine, 2000). In previous studies, GSPs were reported to attenuate the oxidative damage in tissue and organs, such as blood (Evcimen et al, 2020), liver (Miltonprabu et al, 2016), kidney (Nazima et al, 2015), testes (Morsi et al, 2020), brain (El-Tarras et al, 2016), pancreas (Nazima et al, 2016), and prostate (Lei et al, 2017) of rats exposed to dietary Cd. These ameliorative effects of GSPs on cadmium-induced oxidative stress were also shown in mice kidney (Chen et al, 2013) and chicken embryos (Hou et al, 2016).…”
Section: Introductionmentioning
confidence: 97%